PERAN GURU DALAM MEMBIMBING PEMBIASAAN IBADAH MADHAH PADA SISWA-SISWI KELAS II DI MI MA’ARIF PANJENG JENANGAN PONOROGO TAHUN AJARAN 2016/2017 - Ulfa Ummul Maghfiroh; Nurul Iman; Nurul Abidin (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2025)
In MI Ma'arif Panjeng, there are 2nd graders in performing the mahdhah worship practice is still not in accordance with the correct provisions. Like when the prayer is still toll-toleh and criwisan with friends so it does not recite the reading of prayer. Prayer is a special worship in Islam, both seen from the command Muhammad received directly from God and other dimensions. The main rite in the religion of Islam is the prayer that will integrate human life into the spirit and this prayer is also called as the pillar of religion, and the deed of worship that will first be weighed in the next day (akhirat). So there must be perfection in running the prayer, in terms of movement and reading the students are still far from perfection. It should be more we pay attention. A teacher should always have to guide in habituation of students. So the purpose of this study is: to describe the role of teachers in guiding the worship of mahdhah worship in grade 2 students at MI Ma'arif Panjeng Jenangan Ponorogo and to describe the role of the teacher as supervisor in guiding the worship of mahdhah worship in the second grade students at MI Ma 'Arif Panjeng Jenangan Ponorogo. This research uses qualitative approach method, the method used in collecting data is interview, observation, and documentation. The data analysis techniques include data collection and data reduction, display data and conclusion. The results of this study can be concluded:1) Implementation of mahdhah worship practice (dhuha prayer) at MI Ma'arif Panjeng Jenangan Ponorogo. a. Held a schedule of imams and companions habituate prayers dhuha., b. The time policy of praying dhuha practice., c. The purpose of the implementation of prayer dhuha prayer., d. There is guidance about the practice of praying dhuha., e. Provide socialization and supervision., f. Absence., g. The existence of cooperation among teachers., h. Fostering good relationships with learners., i. The existence of sanctions. 2) The impact of mahdhah worship practice at MI Ma'arif Panjeng Jenangan Ponorogo. a. Morals against God: applying gratitude, strengthening faith in Allah SWT and more trust., b. Morals against the human fellow: bridle the rope, have manners on everyone and be able to control the emotions or anger so the heart becomes calm., 3. Teachers as supervisors are supervising the students when the activities of worship in the school so if when the implementation of mahdhah worship service there are students who make mistakes can be directly reprimanded and then directed.